2009
DOI: 10.1007/s00417-009-1213-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macular function and visual fields after membrane blue or infracyanine green staining in vitreoretinal surgery

Abstract: Although there was a significant difference in visual fields between the groups after 3 months in the superior region, there were no more significant differences between the two groups after 6 months. However, due to the decrease in the temporal visual field in some eyes, we conclude that membrane blue is less toxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In particular, ICG is supposed to bring about a dose- and illumination-dependent toxicity [10,11] to the retinal ganglion cells and the retinal pigment epithelium [12,13]. However, regarding the functional outcome of ILM peeling with ICG or BBG after a period of 6 months, no significant differences were found [14]. Therefore, the intention of this study was to examine ultrastructural features on the ILM by ICG or BBG to gain a picture of retinal alterations secondary to membrane peeling.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ICG is supposed to bring about a dose- and illumination-dependent toxicity [10,11] to the retinal ganglion cells and the retinal pigment epithelium [12,13]. However, regarding the functional outcome of ILM peeling with ICG or BBG after a period of 6 months, no significant differences were found [14]. Therefore, the intention of this study was to examine ultrastructural features on the ILM by ICG or BBG to gain a picture of retinal alterations secondary to membrane peeling.…”
Section: Introductionmentioning
confidence: 99%
“…While BBG selectively stains the ILM, staining intensity has been reported to be significantly inferior to that of ICG 9 14 15. A number of methods to promote intraoperative BBG sedimentation, such as dye cooling16 and a solution in 4% polyethylene glycol,4 and 5% glucose17 and visco-BBG18 and heavy-water BBG (BBG-D 2 O) have been suggested. However, the only objective measurement of BBG's staining characteristics with CIELAB scores was evaluated for BBG-D 2 O; objective chromaticity scores suggested that ILM staining is not significantly improved with the new formula 9…”
Section: Discussionmentioning
confidence: 99%
“…13,30,32,33 Trypan blue is generally recommended for the removal of epiretinal tissue rather than for ILM peeling itself, 34 although several clinical studies suggest that TB may be more useful for ILM removal than customarily conceived. [31][32][33][35][36][37] Retinal toxicity has been occasionally reported from in vitro experiments 38 and in vivo studies, 39,40 while other authors found no indications for in vivo toxicity. 16,37,[41][42][43] The presence of ERM overlying the ILM requires a sequential approach.…”
Section: Discussionmentioning
confidence: 99%